ANTEROLATERAL LIGAMENT OF THE KNEE JOINT, ANATOMICAL AND RADIOLOGICAL STUDY - Mustafa, Dr. Amal Yousif Ahmed Elhaj; Elkhish, Dr. Abdullah Bin Galil; Alasmary, Dr. Warda Abdella Mohammed; Ali Sakran, Dr. Ashraf Mohammed Elsayed; Elamin, Dr. Asma Mohammed; Elshazly, Dr. Amal Mahmoud; Abdoh, Dr. Ahlam Omer Amin; Khan, Dr. Mohammad Afzal; Hijazi, Dr. Mohammed Mazhar; Ishfag, Dr. Zareen (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Injuries to the anterior cruciate ligament is very common, and itsreconstruction is one of the most common procedures in orthopaedic surgery. But there are stillproblems with the patients undergoing this reconstruction. So further studies of the characteristics ofthe anterolateral ligament (ALL) of the knee were needed.This study aims at demonstrating the anterolateral ligament of the knee, determining its length, width atthe meniscus attachments, and its origin and insertion, and to identify this ligament on magneticresonance imaging.